Evolving animal-sourced foods and livestock markets - Bachewe, Fantu Nisrane; Minten, Bart; Yimer, Feiruz (International Food Policy Research Institute, 2020)
Chapter 8, “Evolving Animal Sourced Foods and Livestock Markets,” covers the changing situation in livestock marketing systems. The authors find that in many developing countries in which staple foods dominate the composition of diets, higher consumption of animal-sourced foods (ASF) is associated with significant nutritional benefits. Given the importance of prices for consumption decisions in these settings, they analyze ASF price patterns, relying on a large-scale price dataset collected in 116 urban retail markets in Ethiopia. The authors document important seasonal and spatial patterns, and they find, worryingly, that real prices of ASF have been increasing over the past decade by between 32 percent and 36 percent for three major ASFs—milk, eggs, and meat. Similar price increases are noted in rural and urban areas as well as for tradable and nontradable ASFs. This price trend is in contrast with staple cereals for which real prices stayed at similar levels over the past decade. As they estimate that a price increase of this magnitude would reduce consumption of ASF by approximately 25 percent, holding other things constant, it seems that more investments and attention to the production of ASF and the livestock sector are needed to reduce ASF prices and increase their consumption in Ethiopia.